Metabolic syndrome and central retinal artery occlusion - Kosanović-Jaković Natalija; Petrović Lidija; Risimić Dijana; Milenković Svetislav; Matić Danica (Vojnosanitetski Pregled, 2005)
Background. The accumulation of risk factors for central retinal artery occlusion can be seen in a single person and might be explained by the metabolic syndrome. Case report. We presented the case of a 52-year-old man with no light perception in his right eye. The visual loss was monocular and painless, fundoscopy showed central retinal artery occlusion and the laboratory investigation showed the raised erythrocyte sedimentation rate of 105 mm/h and the raised C-reactive protein of 22 mg/l. Specific laboratory investigations and fluorescein angiography excluded the presence of vasculitis, collagen vascular diseases, hypercoagulable state and antiphospholipid syndrome. Conclusion. The patient met all the five of the National Cholesterol Education Program (NCEP) criteria for the metabolic syndrome: hypertension, abnormal lipid profile, abnormal glucose metabolism, obesity and hyperuricemia. Measurement of C-reactive protein is useful for the assessment of therapeutic systemic effect on any abnormality in the metabolic syndrome. Individual therapy for all risk factors in the metabolic syndrome is necessary to prevent complications such as cardiovascular, retinal vascular diseases and stroke.